Analysis of Nurse Competence in Prevention of Nosocomial Infections in Inpatient Ward Umar Wirahadikusumah Hospital - Jesika Theresia Sagala; Iyos Sutresna; Heri Ridwan (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Nosocomial infections are an important indicator of hospital service quality because they increase morbidity, mortality, length of hospital stay, and healthcare costs. The success of nosocomial infection prevention is closely related to nurses’ competencies, including knowledge, skills, attitudes, and professional behavior. This study aimed to analyze nurses’ competencies in the successful prevention of nosocomial infections in the inpatient wards of RSUD Umar Wirahadikusumah Sumedang. Method: This study used a descriptive quantitative design with a survey approach. The population consisted of nurses working in the inpatient wards, with 134 nurses selected as samples using stratified random sampling techniques. Data were collected using an infection prevention and control competency questionnaire that had been tested for validity and reliability. Data were presented in the form of frequency distributions and analyzed using univariate analysis to describe the level of nurses’ competencies. Result: The findings showed that nurses’ competencies in preventing nosocomial infections were generally categorized as high, indicating that nurses possessed adequate competence to support infection prevention efforts in the inpatient wards. Conclusion: The study concludes that nurses’ competencies play an important role in supporting the successful prevention of nosocomial infections in inpatient care settings.